PENGEMBANGAN ALAT PENYIRAM JAGUNG SEMI-OTOMATIS BERBASIS KEBUTUHAN PETANI MODERN MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT - Septiani, Riana; Sundari, Susanti; Hidayat, Ghapur (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2024)
This study investigates the application of Quality Function Deployment (QFD) to design a semi-automatic corn sprayer that better meets the needs of modern farmers. Current standard sprayers often fall short in terms of user-friendliness and efficiency in applying fertilizers or pesticides. The goal of this research is to design a semi-automatic sprayer that optimizes corn plant care, aligning with farmers' preferences while considering ergonomics and safety factors through QFD. The research identified three primary attributes: portability, ease of operation, and material quality. Five key areas for improvement were also found: pipe connections (36.54%), sprinkler type (34.62%), nozzle size (19.23%), sprinkler distance (7.69%), and machine capacity (1.92%), as determined by the House of Quality matrix